Planning Management Implementation to Improve Graduate Quality - Misini, Misini; Abidin, Zainal; Warisno, Andi; Andari, An An; Anshori, M Afif (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
The implementation of educational planning management at the Al Khoiriyah Educational Institution Serang, Indonesia, has the goal of improving the quality of graduates with indicators of competence competitiveness, both intellectual and skill as well as superior social competence of alumni. The management implemented by the educational institution Al Khoiriyah Serang is based on Islamic values. To achieve the expected results, management of educational planning within the educational organization Al Khoiriyah Serang needs to be carried out and implemented as well as possible. This study uses library research by collecting information and data from reference books from similar previous research results, articles, notes, and various journals related to the problem to be solved. Implementation of educational planning in an organization, especially in the educational institution Al Khoiriyah Serang is not easy. There are many problems and obstacles in the existing work culture, so the work of teachers and employees greatly influences the output of the educational institutions that are run. The enthusiasm of the community to join in the education of Al Khoiriyah Serang indicates that the community’s trust in the output produced is recognized as superior.